Effect of anion dimensionality on optical properties: the ∞[B7O10(OH)2] layer in CsB7O10(OH)2vs. the ∞[B7O12] framework in CsBaB7O12. Issue 4 (8th January 2020) - Miao, Zhaohong; Yang, Yun; Wei, Zhonglei; Yang, Zhihua; Pan, Shilie
Abstract : CsB7 O10 (OH)2 with new FBB features a 2D anionic structure whose band gap is about 6.6 eV and CsBaB7 O12 features a 3D anionic structure whose band gap is 5.6 eV. And their simulated birefringence are about 0.08 and 0.05 at 1064 nm, respectively. Abstract : Two new caesium borates, CsB7 O10 (OH)2 and CsBaB7 O12, were synthesized in a high-temperature vacuum system and high-temperature open system, respectively. They all crystallize in the monoclinic space groups, C 2/ c (no. 15) and P 21 / c (no. 14), respectively. Their structures show different dimensional anionic architectures. CsB7 O10 (OH)2 has two-dimensional (2D) ∞ [B7 O10 (OH)2 ] anionic layers with the [B7 O12 (OH)2 ] fundamental building block (FBB) which displays a novel connection mode. CsBaB7 O12 possesses a three-dimensional (3D) ∞ [B7 O12 ] anionic open-framework with the [B7 O15 ] FBB. The characterization of their properties combined with experimental and theoretical methods reveals that the two hepta-borates show differences in their optical properties due to their different optical anisotropies which are influenced by their anionic structures. The former compound CsB7 O10 (OH)2 presents a wide band gap of 6.6 eV and the latter compound CsBaB7 O12 presents a band gap of 5.6 eV, which is smaller than that of CsB7 O10 (OH)2 . The first-principles calculation results suggest that the birefringences are 0.08 and 0.05 at 1064 nm for CsB7 O10 (OH)2 and CsBaB7 O12, respectively. Furthermore, the detailed summaries and structural comparisons have been provided for all available disorder-free mixed alkali- and alkaline-earth metal caesium borates.